PENERIMAAN RETRIBUSI PASAR KABUPATEN LEBONG (Studi Terhadap Jumlah Pedagang Dan Pertumbuhan Ekonomi ) - ELLYA REVOLINA; Yuliani - (UNIVED Press, 2014)
Ellya Revolina, Yuliani; The purpose of this research is todetermine the influence ofthe number of tradersstalls, stalls andgrowingmerchantekonomiterhadapdistrictleviesLebongtahunmarketin2004- 2011is thedatathat I usesecondary dataandsamplingmethodsdoneby purposive sampling methodie the number ofmerchantstalls, stalls andgrowingmerchantekonomiterhadapDistrictleviesLebongtahunmarketin2004- 2011Based onthe calculationresultsobtainedcoefficientof Multiple Determination(R2) for0,972berartithata variablenumber oftradersstalls(X1), the number of traderslos(X¬2) andeconomicgrowth(X3) contributedin influencingmarketlevies(Y) of 97.20% while the remaining2.80% areother variables notexamined in this study. Calculated F value of53,663while the Ftabledengan=0.05is equal to6.590asthe value ofF calculated> Ftable(53,663> 6.590) thenHo is rejected,meaning thatthere is no influenceofthe number of tradersstalls(X1), the number of traderslos(X¬2 )danpertumbuhaneconomy(X3) jointlyagainstleviesmarket(Y) tthe valuefora variablenumber oftradersstalls(X1) is5.015; t valuefora variablenumber oftraderslos(X2) is equal10,357dant valueforthe economicgrowthvariable(X3) is equal to2.3064,130sedangkant tableisbecausethe value oft count>t table(5.015> 2.306; 10.357> 2.306and4.130>2.306) means thatthe variablenumber oftradersstalls(X¬1); number oftraderslos(X2) andeconomicgrowth(X3) partial/individualhas an influence onthe marketlevies(Y). Key words:merchantstalls, traderslos, economicgrowth, marketlevies